“Kakao Math” Business Development Market Research - Indriana Puspita Dewi; Alma Aulia Hanifah; Shahnaz Nurazizah (Journal of Economic and Business Analysis, 2024)
Abstract: The increasingly competitive chocolate industry demands chocolate entrepreneurs to become more creative and innovative. "Kakao Math" is processed chocolate with a unique concept that integrates mathematical themes. However, despite the potential of "Kakao Math" products as processed chocolate, entrepreneurs still lack knowledge about consumer preferences for the product. Therefore, this research aims to analyze market research data and obtain appropriate strategies to increase competitiveness of the “Kakao Math’ processed chocolate business. The method used is by distributing questionnaires to obtain data for market research analysis. The research results show that a total of 72 data were obtained from respondents who filled out the Google Form. Based on the research results, it is known that, firstly, respondent characteristics can be observed from gender, age, education level, pocket money, and income. Secondly, the main factors determining market preferences for chocolate products can be seen from knowledge about chocolate products, preference levels, consumption levels, chocolate size, chocolate quantity, purchase purpose, purchase place, consumption purpose, and reasons for continuous purchases. Thirdly, consumer preferences for chocolate products can be observed from loyalty, interest, and recommendations. Keywords: kakao math product; market research; processed chocolate